2018
DOI: 10.1080/07391102.2018.1439403
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial peptide library screening for discovery of diverse α-glucosidase inhibitors using molecular dynamics simulations and binary QSAR models

Abstract: Human α-glucosidase is an enzyme involved in the catalytic cleavage of the glucoside bond and involved in numerous functionalities of the organism, as well as in the insurgence of diabetes mellitus 2 and obesity. Thus, developing chemicals that inhibit this enzyme is a promising approach for the treatment of several pathologies. Small peptides such as di- and tri-peptides may be in natural organism as well as in the GI tract in high concentration, coming from the digestive process of meat, wheat and milk prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 28 publications
1
40
0
Order By: Relevance
“…The results in Table show that the largest dipole moment occurs at 373 K with a SEF of 1 V/nm. However, studies have reported that alpha‐amylase and trypsin inhibitors are considered as potential antiobesity molecules . Thus, the functional properties of RATI after related processing methods, especially high temperature treatments, are needed to be evaluated in the future.…”
Section: Resultsmentioning
confidence: 99%
“…The results in Table show that the largest dipole moment occurs at 373 K with a SEF of 1 V/nm. However, studies have reported that alpha‐amylase and trypsin inhibitors are considered as potential antiobesity molecules . Thus, the functional properties of RATI after related processing methods, especially high temperature treatments, are needed to be evaluated in the future.…”
Section: Resultsmentioning
confidence: 99%
“…There are studies about peptide inhibitory α-glucosidase where carried out with molecular docking models. According to the Mollica et al [31], the crystallographic ligand acarbose interacts with α-glucosidase in the enzymatic cavity by establishing several hydrogen-bond (H-bond) interactions. In particular, the key interactions involve Asp1157, Asp1279, Lys1460, Arg1510, Asp1526, His1584.…”
Section: Evaluation Of the Activity Of Hydrolysates After The Simulatmentioning
confidence: 99%
“…Mouse vas deferens (NMRI mice, 35-45 g) was prepared as described before [26]. After the preparation vas deferens were suspended in 5 ml organ baths containing Mg 2+ free Krebs buffer (118.1 mM NaCl, 25 mM NaHCO3, 4.7 mM KCl, 11 mM glucose, 1.2 mM KH2PO4, 1.8 mM CaCl2) and aerated with carbogen (O2:CO2=95:5) at 31 C.…”
Section: Mouse Vas Deferens Bioassaymentioning
confidence: 99%